Superior dehydrogenation performance of Mg-based alloy under electropulsing. (May 2021) - Zhang, Guozhu; Qin, Shuyang; Yan, Longge; Zhang, Xinfang
Abstract: As a feasible technological approach to promote the global energy transformation, hydrogen energy has gradually become a hot topic in the world's energy field. In order to solve the problem of the poor dehydrogenation kinetic performance in solid hydrogen storage materials, the effect of electropulsing treatment on the dehydrogenation kinetic performance of magnesium alloy was studied through the analysis of dehydrogenation amount, dehydrogenation rate, phase composition and microstructure. After electropulsing treatment, the initial dehydrogenation temperature was reduced by 39 °C, and the maximum dehydrogenation rate was increased from 7.48 wt.% H2 /h to 14.36 wt.% H2 /h. The electropulsing treatment provides a new idea and method for improving the dehydrogenation kinetic performance of hydrogen storage materials. Graphical abstracts: Image, graphical abstract